Herbal Modification of Allopathic Analgesic Drug (International Journal of Scientific Research in Science and Technology, 2024)
The integration of herbal medicine with allopathic analgesic drugs has gained attention as a strategy to improve pain management outcomes. This systematic review synthesizes the existing literature on herbal modification of allopathic analgesic drugs. Key herbs such as turmeric (Curcuma longa), ginger (Zingiber officinale), and willow bark (Salix spp.) are explored for their analgesic properties and potential synergies with conventional pain medications. Mechanisms of action, pharmacokinetic interactions, and clinical evidence supporting their combined use are discussed. Challenges including standardization, safety, and regulatory considerations are also addressed. This review provides insights into the integration of herbal remedies into allopathic pain management protocols and identifies areas for future research.